Chicken soup for the soul teens talk relationships : stories about family, friends, and love - Canfield, Jack 1944-; Hansen, Mark Victor; Newmark, Amy (Cos Cob, CT Chicken Soup for the Soul Pub. LLC, 2008)
A compilation of true stories written by teenagers, and by adults writing about their teenage years, focusing on teen relationships with parents, friends, crushes, boyfriends and girlfriends.
"Our 101 best stories."
Keywords: Teenagers -- Literary collections; Teenagers' writings; Teenagers -- Conduct of life -- Anecdotes; Teenagers -- Family relationships -- Anecdotes; Dating (Social customs) -- Anecdotes